Kynurenine acts as a signaling molecule to attenuate pulmonary fibrosis by enhancing the AHR-PTEN axis - Yi Wang; Guo-Rao Wu; Huihui Yue; Qing Zhou; Lei Zhang; Long He; Weikuan Gu; Rongfen Gao; Lingli Dong; Huilan Zhang; Jianping Zhao; Xiansheng Liu; et al. (Journal of Advanced Research)
Introduction: Pulmonary fibrosis (PF) is a fatal fibrotic lung disease without any options to halt disease progression. Feasible evidence suggests that aberrant metabolism of amino acids may play a role in the pathoetiology of PF. However, the exact impact of kynurenine (Kyn), a metabolite derived from tryptophan (Trp) on PF is yet to be addressed. Objectives: This study aims to elucidate the role of kynurenine in both the onset and advancement of PF. Methods: Liquid chromatography–tandem mass spectrometry was employed to assess Kyn levels in patients with idiopathic PF and PF associated with Sjögren’s syndrome. Additionally, a mouse model of PF induced by bleomycin was utilized to study the impact of Kyn administration. Furthermore, cell models treated with TGF-β1 were used to explore the mechanism by which Kyn inhibits fibroblast functions. Results: We demonstrated that high levels of Kyn are a clinical feature in both idiopathic PF patients and primary Sjögren syndrome associated PF patients. Further studies illustrated that Kyn served as a braking molecule to suppress fibroblast functionality, thereby protecting mice from bleomycin-induced lung fibrosis. The protective effects depend on AHR, in which Kyn induces AHR nuclear translocation, where it upregulates PTEN expression to blunt TGF-β mediated AKT/mTOR signaling in fibroblasts. However, in fibrotic microenviroment, the expression of AHR is repressed by methyl-CpG-binding domain 2 (MBD2), a reader interpreting the effect of DNA methylation, which results in a significantly reduced sensitivity of Kyn to fibroblasts. Therefore, exogenous administration of Kyn substantially reversed established PF. Conclusion: Our studies not only highlighted a critical role of Trp metabolism in PF pathogenesis, but also provided compelling evidence suggesting that Kyn could serve as a promising metabolite against PF.